Larval exposure to low concentrations of neonicotinoids and niacin affects Drosophila melanogaster indices of reproductive success - Kovach, V.; Filiponenko, N.; Kolot, N.; Volkova, N. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2018)
Since the discovery, neonicotinoids have been considered as the most promising compounds with insecticidal activity due to the specific effect on nicotinic acetylcholine receptors of insects and low toxicity for mammals in the applied concentration ranges, and also because of the lack of resistance formation to them in insects. Neonicotinoids introduction into agricultural practice has resulted in significant increase of different crops yields. However, with the active widespread use of this class of insecticides, a number of negative consequences have been identified, in particular for pollinating insects. The detection of these effects led to a significant restriction or ban on these compounds use in agricultural practices in a number of countries. Ukraine is not among them. Considering that insecticides of this class are freely sold and their use is uncontrolled, the corresponding active substances are constantly present in agroecosystems, and their residual (non-lethal) concentrations can affect the viability and reproduction of insects, both harmful and useful or neutral. This study is an experimental comparative analysis of the effect of residual concentrations of neonicotinoid insecticides and nicotinic acid on Drosophila reproduction. The results of the study have shown that nicotinic acid has a similar (inhibition), but less strong (in comparison with the insecticides used) effect on the fertility and viability of genetically different Drosophila stocks. The genotype-dependent effects of the studied compounds on the lethality at pupa stage have been revealed. It has also been established that among the offspring of individuals who survived under the effect of neonicotinoids and niacin, the proportion of those who survive to the larval stage increases in comparison with the control group. Therefore, depending on the genotype, the long-term (in ontogenesis) effects of neonicotinoids and nicotinic acid at low concentrations may shift the selection in the offspring of exposed individuals from the early embryonic stage towards the parents (i.e., affect gametogenesis and viability of gametes).